Perancangan dan Pengembangan Pencatatan Akuntansi dan Laporan Keuangan pada Love Market Pasar Online - Daniel Apdianto Herman; Hendry Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Love Market Online Market is a market business located in the new Cahaya Garden Building, Sadai, Bengkong. Love Market Online Market has been established since March 2020. The problem in the Love Market Online Market business is the difficulty in making accounting records and financial reports, because it must collect transaction and expense processes manually. Therefore, a system is needed to help facilitate recording and reporting. One of the methods in designing the system to solve the problems encountered is the waterfall method which has stages of analysis, system design, coding, testing, testing, and maintenance. The results of this study will be a web-based accounting record system to facilitate accounting records and financial reports at Love Market Online Market